Enhance Parameter Speed Estimation of Induction Motor Using Modified Voltage Model Flux Estimation - Solly Aryza; zulkarnain lubis (Jurnal Elektro dan Telkomunikasi, 2020)
Enhance Parameter Speed Estimation of Induction Motor Using Modified Voltage Model Flux Estimation